Preparation and Development of Fig Fruit Jam Blended with Different Level of Apple Pulp: Fig Fruit Jam Blended - Khan, Arsalan; Shah, Falak Naz; Zeb, Qamar; Zeeshan, Muhammad; Iqbal, Huzaifa; Noor, Hamid (Biological Sciences - PJSIR, 2020)
Fig is familiar in the World as a edible fruit, but technically it is not a fruit it is a container, called a syconium, which is oddly an inside out flower cluster. The present study was conducted to prepare a value-added product form fig fruit blended with apple pulp. The jam was prepared with different combination of fig pulp and apple pulp, 200:200, 250:150, 300:100, 350: 50 and 400:00. The treatments were analyzed physio-chemically and sensory for a total period of 90 days. The statistical results revealed that treatment have a significant (P<0.05) on physio-chemical and sensory attributes of jam. The physio- chemical study revealed that pH, ascorbic acid and non-reducing sugar decreased significantly, while TSS, reducing sugar and % acidity showed a significant increased during 90 days of storage. In sensory attributes, the control and test samples showed a significant difference in texture, taste and colour. The sensory results indicated that with decreased in the apple pulp the texture properties decreases and the opacity increased. The statistical results showed treatment T1(200:200) was found best among the other treatments followed by T2 (250:150) in chemical and sensory attributes. The new formulated product can serve as a good spread on bread and other etc.